Manusia Terhutang Budi Kepada Nabi Muhammad S.A.W - Abdul Mukti, Mohd Fakhrudin (Jurnal Usuluddin, 2000)
This article is a translation of al-Nadwi’s treatise deals with the contribution of the Prophet, peace be upon him, to the world globally. His divine messages propose the ideas of universal peace, freedom and safety that humankind need all the time. Many prominent Western scholars and historians seem to have appreciated this kind of contribution of Islam to the world.